METAPHORICAL EXPRESSIONS IN EMILY DICKINSON’S POEMS - Lola Cenita; Ely Nurmaily (Linguistics and Literature Students' Journal, 2020)
The poem has the role of the media to deliver the author’s opinion, messages, and feeling towards certain phenomena to the readers by using literary language. The idea of those poems needs to be interpreted by the readers and it is dealing with meaning. Problems occur when there is the literary language used by the author since not all the reader can understand the implicit meaning inside the poems which certainly used figurative language, especially metaphor. Thus, the study entitled Metaphorical Expressions in Emily Dickinson’s Poems aimed to find the metaphor inside three poems by Emily Dickinson entitled I Felt a Funeral in My Brain, Because I could Not Stop for Death and I Heard a Fly Buzz – when I Died. This study also aimed to identify the implicit meaning behind those metaphors. In analyzing the data, the researcher used the metaphor theory proposed by Lakoff and Johnson, they are structural metaphor, ontological metaphor, and orientational metaphor. To answer the second research question, the researcher used the theory of meaning by I. A Richard. This study used a descriptive qualitative method and stylistic approach, in which the researcher focuses on the aesthetic function of the language. In this research, the researcher found 17 metaphorical expressions divided into 5 types of metaphor there are: entity metaphor 4 data, structural metaphor 5 data, orientation metaphor 1 data, container metaphor 1data and personification 6 data.